Pedagogical, Social and Psychological Support for Students with Visual Impairment in a Higher Educational Institution - Tatyana KARANDAEVA; Elena BORISOVА; Irina KOZINA; Venera DENISKINA; Vladimir SOKOLOV (Communications of International Proceedings, 2021)
The article is devoted to organization of pedagogical, social and psychological support for students with visual impairments in a higher educational institution. The article justifies the need for pedagogical, social and psychological support for students with visual impairments. The author considers the goal, tasks, conditions and main directions of the support team. The paper presents psychological features of the cognitive activity of students with visual impairments.
Keywords: Students with Visual Impairments; A Higher Educational Institution; Individual Social and Psychological Support.